2015
DOI: 10.1001/jamaophthalmol.2014.4237
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Precision in a Series of Visual Fields Acquired by the Standard and Fast Versions of the Swedish Interactive Thresholding Algorithm

Abstract: Algorithm (SITA) testing strategies for the Humphrey Field Analyzer have become a clinical standard. Measurements from SITA Fast are thought to be more variable than SITA Standard, yet some clinics routinely use SITA Fast because it is quicker.OBJECTIVE To examine the measurement precision of the 2 SITA strategies across a range of sensitivities using a large number of visual field (VF) series from 4 glaucoma clinics in England.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 26 publications
(38 reference statements)
2
35
0
Order By: Relevance
“…The residual distribution of VF test error is known to be severely skewed toward the negative in areas of significant damage. 51 VF event analysis has a well-characterized low false positive rate of 2.6%, 8 but had relatively low detection rates in this study. Overall, OCT may be a more reliable test for glaucoma progression because it has good detection rate and acceptable specificity over a wide range of glaucoma severity.…”
Section: Discussionmentioning
confidence: 63%
“…The residual distribution of VF test error is known to be severely skewed toward the negative in areas of significant damage. 51 VF event analysis has a well-characterized low false positive rate of 2.6%, 8 but had relatively low detection rates in this study. Overall, OCT may be a more reliable test for glaucoma progression because it has good detection rate and acceptable specificity over a wide range of glaucoma severity.…”
Section: Discussionmentioning
confidence: 63%
“…New technology such as OCT-angiography may further elucidate the disease process and allow better links to be made between how the eye is changing and how it functions [98-100]. Further, changes in test algorithms [101, 102], stimulus size [103, 104] and location [105-107] as well as analysis methods [108-112] of visual field measurements may help deal with the noise that currently obfuscates interpretation of visual function measurements. For example, an analytical method called ANSWERS has showed particular promise in this regard, allowing increased test-retest variability with disease severity to be taken into consideration when measuring rates of progression [110, 111].…”
Section: Five Year Viewmentioning
confidence: 99%
“…Fifth, the high myopia registry study had chosen 24-2 SITA fast testing strategy which may be a possible limitation for those who use 24-2 SITA standard. However, it is unlikely as a study by Saunders21 demonstrated that SITA fast and SITA standard result differences were similar and only small differences were found at low sensitivity values. Thus having used SITA fast would not significantly affect our classification system.…”
Section: Discussionmentioning
confidence: 98%
“…SITA strategy has become the most commonly used in glaucoma diagnosis due to its time saving without reducing its effectiveness 19. Two studies20 21 indicated that SITA standard strategy was less variable and more precise than SITA fast in patients with glaucoma, but only for low sensitivity spots. Most of the high myopes were normal, so SITA fast was a better choice.…”
Section: Discussionmentioning
confidence: 99%